EKSISTENSIALISME DAN PENDIDIKAN ISLAM: MENGHADAPI TANTANGAN DALAM MENGEMBANGKAN POTENSI SISWA - Erfin Walida Rahmania (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2025)
This article discusses the integration of existentialism values into Islamic education, particularly in the context of developing students' potential. Existentialism, as a philosophical movement emphasizing individual freedom, the search for meaning in life, and personal responsibility, offers a distinct approach to education that is more authentic and based on free thinking. On the other hand, Islamic education emphasizes the importance of morality, piety, and social responsibility in all aspects of learning. This article examines how these two perspectives can be integrated within Islamic education, identifying both the opportunities and challenges encountered in its application. The opportunities found include providing space for students' personal development, while the main challenge lies in balancing free thinking with religious obligations. The article suggests the implementation of a flexible curriculum based on students' interests, as well as the development of an approach that combines individual freedom with Islamic values, guiding students toward a meaningful and responsible life. Keyword: Keywords: Existentialism; Islamic Education; Student Potential